Human microbiome-derived peptide affects the development of experimental autoimmune encephalomyelitis via molecular mimicryResearch in context - Xin Ma; Jian Zhang; Qianling Jiang; Yong-Xin Li; Guan Yang (EBioMedicine)
Summary: Background: Gut commensal microbiota has been identified as a potential environmental risk factor for multiple sclerosis (MS), and numerous studies have linked the commensal microorganism with the onset of MS. However, little is known about the mechanisms underlying the gut microbiome and host-immune system interaction. Methods: We employed bioinformatics methodologies to identify human microbial-derived peptides by analyzing their similarity to the MHC II-TCR binding patterns of self-antigens. Subsequently, we conducted a range of in vitro and in vivo assays to assess the encephalitogenic potential of these microbial-derived peptides. Findings: We analyzed 304,246 human microbiome genomes and 103 metagenomes collected from the MS cohort and identified 731 nonredundant analogs of myelin oligodendrocyte glycoprotein peptide 35–55 (MOG35-55). Of note, half of these analogs could bind to MHC II and interact with TCR through structural modeling of the interaction using fine-tuned AlphaFold. Among the 8 selected peptides, the peptide (P3) shows the ability to activate MOG35-55-specific CD4+ T cells in vitro. Furthermore, P3 shows encephalitogenic capacity and has the potential to induce EAE in some animals. Notably, mice immunized with a combination of P3 and MOG35-55 develop severe EAE. Additionally, dendritic cells could process and present P3 to MOG35-55-specific CD4+ T cells and activate these cells. Interpretation: Our data suggests the potential involvement of a MOG35-55-mimic peptide derived from the gut microbiota as a molecular trigger of EAE pathogenesis. Our findings offer direct evidence of how microbes can initiate the development of EAE, suggesting a potential explanation for the correlation between certain gut microorganisms and MS prevalence. Funding: National Natural Science Foundation of China (82371350 to GY).